Flow Learning Experience: Applying Marketing Theory to Serious Game Design. (April 2019) - Wang, Chung-Hsiang; Wu, Ko-Chiu; Tsau, Saiau-Yue
The aim of this study was to design a digital game that imparts the concept of urban heat island effects to aid in environmental education. Within the play-time limits, gamers must be alert to signs of warning from the environment and keep the balance between economic growth and the temperature of the environment, so they can safely manage the development of a virtual city. We investigated gamers' learning efficiency in terms of a city's development scale, socioeconomics and the environment, environmental sustainability, increasing areas of green metropolitan space, and heat management of environmental knowledge and gaming experience through a survey of 209 sixth graders. Interestingly, results indicate that heavy gamers are less interested in serious games; they exhibit shorter periods of concentration and lower levels of immersion. If an individual exhibits a high level of fluency in the dimensions of challenge, player skills, control, and clear goals, then she or he is able to acquire knowledge through message involvement when gaming. This allows a serious game to appear less didactic and more fun. This study explored the means by which gamers acquire procedural and descriptive knowledge related to environmental protection through gameflow and immersion.